Conservative and surgical treatment and possible complications of lateral support syndrome of the patellofemoral joint - Daria Kurtyka; Blanka Budziejko; Aleksandra Białkowska; Oliwia Cywińska; Gracjan Różański; Anna Maria Dobosiewicz; Nataliia Badiuk (Kazimierz Wielki University, 2018)
The knee joint is the largest joint in the human body. At the same time, it is most sensitive to various diseases, often leading to the destruction of anatomical structures, disruption of static and dynamic functions. The authors of the article conducted a literary search on the methods of treatment of the syndrome of lateral support of the patellar-hip joint. In the case of lateral support syndrome of the patella and thigh joint, conservative treatment should be implemented first. Properly selected physiotherapeutic methods allow to reduce pain and avoid surgery. Surgical treatment should be the final choice, as it is associated with the possibility of complications that will delay the patient's recovery.